Sistem Pertanggungan Pada Penjaminan Bancassurance oleh Asuransi X Syariah Menurut Konsep Kafālah - Zahara, Nuraiza (TAWAZUN: Journal of Sharia Economic Law, 2020)
Cooperation agreement between the Bank and Insurance in the form of a bancassurance system the Bank transfers part of the risk that will arise to the Insurance. Such as the risk of debtor customer financing bottlenecks due to death, the risk borne by the Bank is transferred to the insurance company with life insurance coverage. Insurance agreement for debtor customers, Insurance applies a system based on the kafālah concept. This study explores how the insurance system between the customer and the Bank with the involvement of Insurance as a guarantor in the Bancassurance agreement and how the Islamic legal review of the insurance system carried out by the Insurance against the Bank with the Bancassurance agreement. This research uses descriptive analysis method, which describes or gives a description of the object under study through data or samples that have been collected. The conclusion of the research is that the coverage applied by the Insurance against the Bank is not in accordance with the true kafālah concept, the Insurance has paid the principal fund fully but does not pay the service fee in accordance with the minimum amount determined by the Bank. Based on the concept of insurance, the insurance should be obliged to fulfill everything that is the responsibility of the customer to the Bank, including compensation for services as stipulated. From the explanation above, the concept of kafālah applied by Insurance in its coverage of the Bank is still a mismatch between the concept and its application.